(untitled) (Research, Society and Development, 2020)
Objective: to describe the management of erosive tooth wear (ETW) using a digital technology CAD-CAM (computer-Aided Design). Methodology: case report of a 50-year-old female who sought care at a private dental clinic complaining of pain in the teeth. The diagnosis of ETW was carried out using the BEWE index (Basic Erosive Wear Examination), which detect the presence of erosive lesions and identified the diet as the main factor responsible for the problem. The patient received instructions on eating habits and oral hygiene and was done to restore tooth 44, which has erosive lesions on the dentin, using digital technology. Conclusion: the manufacture of ceramic restorations, the use of CAD-CAM technology is another alternative for the treatment of erosive lesions in the dental structure.